2018
DOI: 10.1371/journal.pcbi.1006382
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of early afterdepolarization properties in ventricular myocyte models

Abstract: Early afterdepolarizations (EADs) are spontaneous depolarizations during the repolarization phase of an action potential in cardiac myocytes. It is widely known that EADs are promoted by increasing inward currents and/or decreasing outward currents, a condition called reduced repolarization reserve. Recent studies based on bifurcation theories show that EADs are caused by a dual Hopf-homoclinic bifurcation, bringing in further mechanistic insights into the genesis and dynamics of EADs. In this study, we invest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 72 publications
2
22
0
Order By: Relevance
“…In the diagram for the slow gating variable-parameterized fast subsystem with a superimposed full system trajectory, gradual increases in the slow variable led the full system trajectory slowly across the stable steady-state branch of qEP and then into the region of the stable periodic branch of qLC through an HB point, resulting in the termination of EADs via a homoclinic bifurcation of qLC. This scenario is known as the Hopf-homoclinic bifurcation mechanism (Tran et al, 2009;Qu et al, 2013;Song et al, 2015;Huang et al, 2018). Consistent with these previous reports, the mTP06b model exhibited slow I Ks activationdependent EADs in the xs 2 regions of stable and unstable qEPs ( Figure 7A); however, a stable qLC region or homoclinic bifurcation to yield EAD termination was not detected for the fast subsystem of the mTP06b model.…”
Section: Ead Termination Mechanisms (Roles Of I Ks I Kr and I Cal )supporting
confidence: 88%
“…In the diagram for the slow gating variable-parameterized fast subsystem with a superimposed full system trajectory, gradual increases in the slow variable led the full system trajectory slowly across the stable steady-state branch of qEP and then into the region of the stable periodic branch of qLC through an HB point, resulting in the termination of EADs via a homoclinic bifurcation of qLC. This scenario is known as the Hopf-homoclinic bifurcation mechanism (Tran et al, 2009;Qu et al, 2013;Song et al, 2015;Huang et al, 2018). Consistent with these previous reports, the mTP06b model exhibited slow I Ks activationdependent EADs in the xs 2 regions of stable and unstable qEPs ( Figure 7A); however, a stable qLC region or homoclinic bifurcation to yield EAD termination was not detected for the fast subsystem of the mTP06b model.…”
Section: Ead Termination Mechanisms (Roles Of I Ks I Kr and I Cal )supporting
confidence: 88%
“…However, phase‐3 EADs and TAs have been rarely observed in isolated ventricular myocytes [low amplitude phase‐3 EADs with take‐off potential around −50 mV but not TAs were reported in isolated mice ventricular myocytes (Edwards et al, 2014; Tazmini et al, 2020)]. This was supported by a literature survey by Huang et al (Huang et al, 2018), which showed that the vast majority of the EADs recorded in experiments of isolated ventricular myocytes are phase‐2 EADs (see table 1 in Huang et al), no phase‐3 EADs and TAs were observed. Moreover, phase‐3 EADs and TAs were also not observed in computer simulations of ventricular AP models, and only phase‐2 EADs were reported [see EAD takeoff potentials in our previous study for different AP models (Huang et al, 2018), as well as EADs shown in many other computer simulation studies (Clancy & Rudy, 1999; Kurata et al, 2017, 2020; Pueyo et al, 2011; Song et al, 2015; Tanskanen et al, 2005; Varshneya et al, 2018)].…”
Section: Introductionmentioning
confidence: 70%
“…Early afterdepolarizations (EADs) occur during the plateau phase of the cardiac AP and are associated with LQTS and ventricular tachyarrhythmias (associated with HF) (Landstrom et al, 2017). They are triggered by a reduction in repolarization reserve as a result of an increase in an inward current or a decrease in an outward current (Huang et al, 2018). A main contributor to EAD initiation is an increase in L-type Ca 2+ current (I CaL ) which drives the EAD upstroke.…”
Section: The Role Of Ca 2+ In Arrhythmia Developmentmentioning
confidence: 99%